Violation of Human Rights in The Perspective of The Sociology of Law Judiciary in Indonesia - Jamillah Jamillah (International Asia Of Law and Money Laundering, 2022)
Protection of Human Rights (HAM) is one of the characteristics of the rule of law. Violation of the right to life is a serious Human Rights violation that is qualified as a crime against humanity and a crime of genocide. Indonesia has enacted UU No.26 Tahun 2000 on Human Rights Courts as the basis for establishing a retroactive Ad Hoc Human Rights Court. Settlement of past gross human rights violations through the courts has been conducted in the 1999 East Timor case and the Tanjung Priok case in 1984. Both cases were terminated